Melting Time, Total Solids, Vitamin C, Hedonic Quality Test of Color, Aroma, Sweet Taste and Overall Soursop Velva (Annona muricata L.) with Various Levels of Carrageenan Concentration - Sayyidah Ghaisani Putri; Yoyok Budi Pramono; Antonius Hintono (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2021)
This study aims to determine the effect of variations in the concentration of carrageenan on melting time, total solids, vitamin C and hedonic quality test of soursop velva. The materials used in this study were soursop, mineral water, carrageenan, sugar and citric acid. Carrageenan was added in different concentrations, i.e., 0%, 0.25%, 0.50%, 0.75% and 1% (w/w). Further, quality attributes of soursop velva were evaluated, including its melting time, total solids, vitamin C and hedonic quality test. Melting time was measured using a stopwatch, total solids were analyzed using an oven, vitamin C was analyzed using spectrophotometry UV-VIS and hedonic quality test was performed by panelists. The measurement showed a significant difference (P<0.05) in total solids, hedonic quality of color, aroma and overall soursop velva as a result of different carrageenan concentrations. However, the melting time and sweet taste of soursop velva did not show significant differences (P>0.05). The most optimal use of carrageenan concentration in soursop velva is 0.25% because it has a soft texture, long melting time and is most preferred.